Evaluation of an e-learning module under different tutorial guidance - Jessica Jahn; Andreas Moeltner; Stefan Rüttermann; Susanne Gerhardt-Szép (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
This multivariate, prospective, monocentric, single blind, observational study evaluates the experimental application of an interactive e-learning module under different tutorial guidance on the topic of EbD (Evidence based Dentistry). The voluntary extracurricular module was offered to dentistry students (n=53) during the fi rst clinical semesters. During a processing time of 4 weeks the students were supervised in small groups with an e-tutor (electronic tutor) via e-mail. The tutor supervised n=26 in a facilitative (f) and n=27 non-facilitative (nf) mode. In a fi nal evaluation n=47 students participated, subdivided into n=24 (f) and n=23 (nf). The questionnaire used in the study comprised 10 items assigned to the evaluation of e-learning settings and tutoring effectiveness.